Colposcopic evaluation of cervical lesions: a prospective study - Gupta, Vineeta; Tandon, Archna; Nanda, Anuja; Sharma, Arti; Bansal, Neeta (International Journal of Clinical Trials, 2014)
Background: The present study was undertaken to evaluate the role of colposcopy as a screening and diagnostic tool for cervical cancer and other cervical lesions in high risk women. Methods: All the women included in the study were subjected to colposcopic examination. Colposcopic findings were compared with cytology and histopathological examination. Accuracy of colposcopic examination was calculated by standard statistical methods. Sensitivity, specificity, Positive Predictive Valve (PPV) and Negative Predictive Valve (NPV) of colposcopic examination was calculated. Results: Three hundred patients underwent colposcopic examination. The overall sensitivity and specificity of colposcopy was 85.85% and 87.65% respectively. Positive predictive value was 75.83% and negative predictive value was 95.38%. The percentage of false negative as well as that of false positive was calculated to be 13.74%. The accuracy of colposcopy was found to be more for high grade lesions as composed to low grade lesions. Conclusions: Colposcopy gives immediate and accurate results and its value as diagnostic modality is undisputed. It should also be considered as a primary screening test for high risk women living in remote areas where women cannot visit the doctor repeatedly as the ideal screening triage cannot be implemented in such situations.